2010
DOI: 10.1038/nm.2127
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 and high-mobility group box-1 are involved in ictogenesis and can be targeted to reduce seizures

Abstract: Brain inflammation is a major factor in epilepsy, but the impact of specific inflammatory mediators on neuronal excitability is incompletely understood. Using models of acute and chronic seizures in C57BL/6 mice, we discovered a proconvulsant pathway involving high-mobility group box-1 (HMGB1) release from neurons and glia and its interaction with Toll-like receptor 4 (TLR4), a key receptor of innate immunity. Antagonists of HMGB1 and TLR4 retard seizure precipitation and decrease acute and chronic seizure rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
884
3
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 816 publications
(962 citation statements)
references
References 55 publications
57
884
3
7
Order By: Relevance
“…Mice were surgically implanted with an injection guide cannula and recording electrodes under deep Equithesin anesthesia and stereotaxic guidance [11,25]. Two Nichrome-insulated bipolar depth electrodes (60 μm OD; MOR Electric Heating Assoc.…”
Section: Mouse Model Of Acute Seizuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Mice were surgically implanted with an injection guide cannula and recording electrodes under deep Equithesin anesthesia and stereotaxic guidance [11,25]. Two Nichrome-insulated bipolar depth electrodes (60 μm OD; MOR Electric Heating Assoc.…”
Section: Mouse Model Of Acute Seizuresmentioning
confidence: 99%
“…Intrahippocampal injection of kainic acid in freely moving mice was done 7 days after surgery as previously described [11,25]. Kainic acid (7 ng in 0.5 μl; Sigma, Saint Louis, MO) was dissolved in 0.1 M phosphate-buffered solution (PBS, pH 7.4) and injected unilaterally in the dorsal hippocampus by using a needle protruding 2.0 mm from the bottom of the guide cannula.…”
Section: Mouse Model Of Acute Seizuresmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that IL-1β and high-mobility group box 1 (HMGB1) were simultaneously synthesized and released by astrocytes and microglia in the brain of the mice seizure models. Notably, a rapid release of HMGB1 from neurons appears to be triggered by proconvulsant drugs even before seizure occurrence and is involved in their precipitation of seizures [39]. IL-1 is also involved in the synthesis of IL-6 and TNF-α [40].…”
Section: Roles Of Immune and Inflammation In Drementioning
confidence: 99%